2021
DOI: 10.1002/jsfa.11324
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial community, physiochemical indices, and volatile compounds of Chinese te‐flavor baijiu daqu produced in different seasons

Abstract: BACKGROUND: Chinese te-flavor baijiu (CTF), the most famous Chinese baijiu in Jiangxi province, China, is made from a unique daqu. Its characteristic style is closely related to the daqu used for fermentation. However, current studies on the effects of different production seasons on microbial communities, physicochemical indices, and volatile compounds in CTF daqu are very rare.RESULTS: The relationships of microbial communities, physicochemical indices, and volatile compounds in CTF daqu produced in summer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
(35 reference statements)
1
25
0
Order By: Relevance
“…Due to the open fermentation, seasonal dynamics on climate may introduce differences in biodiversity and richness of microorganisms in the raw materials and environment. For example, the characteristics of Shanxi mature vinegar ( Kou et al, 2022 ), Fuyu-flavor Baijiu ( Kang et al, 2022 ), and Chinese te-flavor baijiu Daqu ( Fu et al, 2021 ) were reported to be affected by seasonal variation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the open fermentation, seasonal dynamics on climate may introduce differences in biodiversity and richness of microorganisms in the raw materials and environment. For example, the characteristics of Shanxi mature vinegar ( Kou et al, 2022 ), Fuyu-flavor Baijiu ( Kang et al, 2022 ), and Chinese te-flavor baijiu Daqu ( Fu et al, 2021 ) were reported to be affected by seasonal variation.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang‐flavor Daqu could provide Jiang‐flavor components and precursor substances for Baijiu production (Wang et al, 2017), yet the production of Daqu mainly relies on sensory evaluation of enologists to make the fermentation proceed normally, which is full of uncertainty and subjective (Fu et al, 2021). Thus, clarifying the primary microorganisms in Daqu is one of the urgent problems to the control of product stability.…”
Section: Discussionmentioning
confidence: 99%
“…The volatile compounds were extracted with a 50/30 μm DVB/CAR/ PDMS fiber (Supelco Corporation). One gram of sample and 8 μl 4-methyl-2-pentanol (Fu et al, 2021) internal standards (1.6152 mg/ ml) was placed into a 15 ml vial, tightly capped with a silicon septum, equilibrated at 60°C in a thermostatic bath for 15 min and extracted for 50 min at the same temperature. After extraction, the fiber was immediately introduced into the injection port of gas chromatography-mass spectrometry to thermally desorb the analyte at 270°C for 3 min (Thermo trace 1300 Gas chromatograph system combined with a TSQ 9000 mass spectrometer, Thermo Electron Corporation, equipped with a VF-WAX-MS capillary column, 30.0 m × 0.25 mm, 0.25 μm, Agilent Corporation).…”
Section: Analysis Of Volatile Compounds In Daqu By Headspace Solid-ph...mentioning
confidence: 99%
“…The aromatic components of te-flavored baijiu have the following characteristics: rich in odd-carbon fatty acid ethyl ester, with the greatest quantity among all types of aromatic baijiu. The esters in special-flavored baijiu are mainly ethyl propionate, and also ethyl valerate, ethyl heptanoate, and ethyl pelargonate; volatile compounds are ethyl acetate and ethyl hexanoate, in equilibrium with heptyl ester ( Fu et al, 2021 ).…”
Section: Flavor Types and Fermentation Microorganisms Of Chinese Baijiumentioning
confidence: 99%